Slow node open-circuit high-temperature-resistant composite diaphragm and preparation method thereof, and laminated silicon-based ternary lithium battery
By introducing fluoride self -extinguishing polymer layers and ceramic coatings in the septum of the silicon -based ternary lithium battery to form a slow -moving high -temperature composite diaphragm of a slow -moving node, it solves the problem of heat out of control and the battery during acupuncture. The problem of high combustion of the diaphragm has achieved the battery's high -efficiency acupuncture test.
Patent Information
- Application Number
- CN202411461528.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
AI Technical Summary
Laminated silicon-based ternary lithium batteries are prone to cause heat loss when needle-punched, and the existing diaphragm has high combustibility and cannot pass the needle-punching test effectively.
A slow -temperature -resistant high -temperature composite diaphragm is used, which includes a base membrane, a fluorine -containing self -extinguished polymer layer and ceramic coating. The fluorine self -extinguished polymer layer will shrink and melt to form a disconnection under high temperature conditions. Ceramics The coating has the characteristics of high temperature stability and delaying increased heat.
A large area of combustion caused by the combustion of the diaphragm is effectively suppressed, ensuring that the battery does not form a short circuit in the acupuncture test, and improves the safety and high temperature resistance of the battery.
Smart Images

Figure CN119361971A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of laminated silicon-based ternary lithium batteries, and in particular to a slow node disconnection high-temperature resistant composite diaphragm and a preparation method thereof, and a laminated silicon-based ternary lithium battery. Background Art
[0002] At present, when laminated silicon-based ternary lithium batteries are punctured, they are prone to thermal runaway because the ternary materials generate heat and release active oxygen when short-circuited; at the same time, the silicon-based negative electrode contained in the laminated silicon-based ternary lithium battery has a higher activity than the carbon negative electrode after lithium is embedded, and safety is more difficult to pass. Therefore, the puncture test of laminated silicon-based ternary lithium batteries has always been a bottleneck that is difficult to break through.
[0003] For example, Chinese patent document No. CN 116247371 A discloses a method for preparing a coated separator with high temperature resistance and puncture resistance, in which the added boron phenolic resin is evenly mixed with ceramic particles to form a high temperature resistant coating, so that the dense coating layer is conducive to improving the needle puncture strength, that is, the boron phenolic resin is cross-linked and cured to form a boron phenolic resin skeleton, which inhibits the thermal shrinkage of the separator and avoids internal short circuit caused by direct contact between the positive and negative electrodes.
[0004] Although the introduction of boron phenolic resin into the above-mentioned diaphragm can effectively improve the heat resistance of the diaphragm, since boron phenolic resin is still easy to burn at high temperatures, it still cannot meet the requirements of the needle puncture test of laminated silicon-based ternary lithium batteries. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and to provide a slow node disconnection mode that can form a disconnection and disconnection at the positive and negative electrode puncture points, which effectively suppresses the problem that the traditional slow node disconnection high-temperature resistant composite diaphragm and its preparation method cannot pass the puncture test due to large-scale combustion caused by the high flammability of the diaphragm, as well as a laminated silicon-based ternary lithium battery.
[0006] The purpose of this disclosure is achieved through the following technical solutions:
[0007] A slow node breaking high temperature resistant composite diaphragm comprises a base film, a fluorine-containing self-extinguishing polymer layer and a ceramic coating, wherein the fluorine-containing self-extinguishing polymer layer and the ceramic coating are respectively arranged on the two sides of the base film, and the fluorine-containing self-extinguishing polymer layer is used to shrink and melt the slow node breaking high temperature resistant composite diaphragm when it is punctured by a needle, and form a circuit at the puncture position.
[0008] In one embodiment, the fluorine-containing self-extinguishing polymer layer includes at least one of PVDF polymer, polytetrafluoroethylene and polyperfluoroethylene propylene.
[0009] In one embodiment, the molecular weight of the PVDF polymer is 400,000 Da to 500,000 Da.
[0010] In one embodiment, the ceramic coating includes at least one of LATP and LLZO.
[0011] In one embodiment, the thickness of the fluorine-containing self-extinguishing polymer layer is 2 μm to 3 μm; and / or,
[0012] The fluorine-containing self-extinguishing polymer layer is a high temperature resistant porous fluorine-containing self-extinguishing polymer layer.
[0013] In one embodiment, the base film is a PE base film or a PP base film.
[0014] A method for preparing a slow node breaking high temperature resistant composite diaphragm comprises the following steps:
[0015] Obtaining basement membrane;
[0016] Performing a corona treatment on the base film to obtain a corona base film;
[0017] preparing a first electrospinning solution containing a fluorine-containing self-extinguishing polymer;
[0018] Performing a first electrospinning operation on the first surface of the corona base film using the first electrospinning solution to form a fluorine-containing self-extinguishing polymer layer on the first surface of the corona base film;
[0019] preparing a second electrospinning solution containing ceramics;
[0020] The second electrospinning liquid is used to perform a second electrospinning operation on the second surface of the corona base film to form a ceramic coating on the second surface of the corona base film, so as to obtain the slow node breaking high temperature resistant composite diaphragm described in any of the above embodiments.
[0021] In one of the embodiments, before the step of performing corona treatment on the base film, the method for preparing the slow node disconnection high temperature resistant composite diaphragm further comprises the following step: performing surface treatment on the base film.
[0022] In one embodiment, the conditions of the first electrospinning operation are: the first voltage is 10 kV to 25 kV, the first spinning distance is 15 cm to 20 cm, and the first extrusion speed is 0.02 mL / min to 0.3 mL / min; and / or,
[0023] The conditions of the second electrospinning operation are as follows: the second voltage is 10 kV to 25 kV, the second spinning distance is 15 cm to 20 cm, and the second extrusion speed is 0.02 mL / min to 0.3 mL / min.
[0024] A laminated silicon-based ternary lithium battery comprises a positive electrode sheet, a silicon-based negative electrode sheet and a diaphragm which are stacked in sequence, wherein the diaphragm is prepared by using the slow node disconnection high temperature resistant composite diaphragm described in any of the above embodiments.
[0025] Compared with the prior art, the present invention has at least the following advantages:
[0026] 1) Compared with the traditional boron phenolic resin, the fluorine-containing self-extinguishing polymer layer contains fluorine atoms, which have high electronegativity and low polarizability, so that the interaction between the molecular chains of the fluorine-containing self-extinguishing polymer layer is strong and not easy to burn. In addition, the presence of fluorine atoms also improves the chemical resistance and thermal stability of the fluorine-containing self-extinguishing polymer layer, and because the fluorine-containing self-extinguishing polymer layer itself has self-extinguishing properties, when the laminated silicon-based ternary lithium battery is punctured, the fluorine-containing self-extinguishing polymer layer at the puncture site shrinks and melts under high temperature conditions and forms a short circuit, that is, the positive and negative puncture sites form a slow node disconnection mode with a short circuit, thereby effectively suppressing the problem that the traditional diaphragm cannot pass the puncture test due to large-scale combustion caused by high flammability.
[0027] 2) Since the fluorine-containing self-extinguishing polymer layer usually has high flexibility and relatively low mechanical strength, when passing the puncture test, if the diaphragm of the simple fluorine-containing self-extinguishing polymer layer is easily deformed or broken, there is still the problem of short circuit at the puncture site, that is, it cannot pass the puncture test. Therefore, the ceramic coating added in the present disclosure has the characteristics of high temperature stability and delayed heat increase, so that the fluorine-containing self-extinguishing polymer layer at the puncture site undergoes rapid high-temperature shrinkage and melting under high temperature conditions to form a break point, and after high-temperature shrinkage and melting, the fluorine-containing self-extinguishing polymer layer can cover the inner peripheral wall of the puncture site, not only quickly forming a break at the periphery of the puncture site, but also improving the close combination with the ceramic coating at the puncture site, so as to ensure that the ceramic coating at the puncture site can significantly delay the rapid increase of heat during the puncture process, avoid the phenomenon of burning at the puncture site in a short time, and better solve the problem that the laminated silicon-based ternary lithium battery cannot pass the puncture test in practical applications.
[0028] 3) In addition, the added fluorine-containing self-extinguishing polymer layer is also beneficial during the formation stage. As the formation temperature increases, the surface softening can occur, so that the fluorine-containing self-extinguishing polymer layer can effectively inhibit the expansion and peeling of the silicon-carbon material, and as the formation temperature decreases, it becomes hard and is beneficial to the shrinkage of the silicon-carbon material after lithium removal, so as to facilitate the preparation of high-performance and high-rate laminated silicon-based ternary lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 This is a flow chart of a slow node disconnection high temperature resistant composite diaphragm according to an embodiment of the present invention;
[0031] Figure 2 This is a practical comparison diagram of the laminated silicon-based ternary lithium battery before and after the needle penetration test of Example 1 of the present invention. DETAILED DESCRIPTION
[0032] In order to facilitate the understanding of the present disclosure, the present disclosure will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present disclosure are given in the drawings. However, the present disclosure can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present disclosure more thoroughly and comprehensively understood.
[0033] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present disclosure. The terms used herein in the specification of the present disclosure are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0035] See also Figure 1 In order to better understand the technical solutions and beneficial effects of the present invention, the present invention is further described in detail below in conjunction with specific embodiments:
[0036] A slow node disconnection high temperature resistant composite diaphragm according to one embodiment comprises a base film, a fluorine-containing self-extinguishing polymer layer and a ceramic coating, wherein the fluorine-containing self-extinguishing polymer layer and the ceramic coating are respectively arranged on two sides of the base film, and the fluorine-containing self-extinguishing polymer layer is used to shrink and melt the slow node disconnection high temperature resistant composite diaphragm when it is punctured, and to form a disconnection at the puncture position.
[0037] It is understandable that due to the characteristics of the laminated lithium battery's own design, the laminated lithium battery has a lower internal resistance, and under the same voltage, the current of the laminated lithium battery will be greater, which causes the problem of easy short circuit at the puncture point and the inability to achieve the puncture test. Therefore, there are also some high-temperature resistant and puncture-resistant coated diaphragms on the market, just as the boron phenolic resin and ceramic particles involved in the background technology are evenly mixed to form a high-temperature resistant coating; for example, Chinese patent document No. CN 115473006 B discloses a polyimide composite diaphragm and its preparation method and sodium ion battery. However, for ternary lithium batteries containing highly active silicon-based negative electrode sheets, the above-mentioned boron phenolic resin and polyimide are relatively flammable, and still cannot effectively suppress the problem of large-area burning short circuit during the ternary lithium battery puncture test of silicon-based negative electrode sheets.
[0038] Therefore, in the present disclosure, a fluorine-containing self-extinguishing polymer layer is provided on one side of the base film. Compared with the traditional boron phenolic resin or polyimide, the fluorine-containing self-extinguishing polymer layer contains fluorine atoms, which have high electronegativity and low polarizability, so that the interaction force between the molecular chains of the fluorine-containing self-extinguishing polymer layer is strong and not easy to burn. In addition, the presence of fluorine atoms also improves the chemical resistance and thermal stability of the fluorine-containing self-extinguishing polymer layer, and because the fluorine-containing self-extinguishing polymer layer itself has self-extinguishing properties, when the laminated silicon-based ternary lithium battery is punctured, the fluorine-containing self-extinguishing polymer layer at the puncture position shrinks and melts under high temperature conditions and forms a short circuit, that is, the positive and negative puncture positions form a slow node short circuit mode with a short circuit and no connection, thereby effectively suppressing the problem that the traditional diaphragm cannot pass the puncture test due to large-scale combustion caused by high flammability.
[0039] It can also be understood that since the fluorine-containing self-extinguishing polymer layer usually has high flexibility but relatively low mechanical strength, when passing the needle puncture test, if the diaphragm of the fluorine-containing self-extinguishing polymer layer alone is prone to deformation or rupture, there is still the problem of short circuit formation at the needle puncture point, that is, it cannot pass the needle puncture test. Therefore, the present invention discloses a ceramic coating added on the other side of the base film, so that the fluorine-containing self-extinguishing polymer layer and the ceramic coating are respectively arranged on the two sides of the base film. Since the ceramic coating has high-temperature stability and the characteristics of delaying heat increase, the fluorine-containing self-extinguishing polymer layer at the puncture site undergoes rapid high-temperature shrinkage and melting under high-temperature conditions to form a break point, and after the high-temperature shrinkage and melting, the fluorine-containing self-extinguishing polymer layer can cover the inner wall of the puncture site, not only quickly forming a break at the periphery of the puncture site, but also improving the close bonding with the ceramic coating at the puncture site, so as to ensure that the ceramic coating at the puncture site can significantly delay the rapid increase of heat during the puncture process, avoid the phenomenon of burning at the puncture site in a short time, and better solve the problem that the stacked silicon-based ternary lithium battery cannot pass the puncture test in practical applications.
[0040] It can also be understood that the added fluorine-containing self-extinguishing polymer layer is also beneficial during the formation stage. As the formation temperature increases, the surface softening can occur, so that the fluorine-containing self-extinguishing polymer layer can effectively inhibit the expansion and peeling of the silicon-carbon material, and as the formation temperature decreases, it becomes hardened and is conducive to the shrinkage of the silicon-carbon material after lithium removal, so as to facilitate the preparation of high-performance and high-rate laminated silicon-based ternary lithium batteries.
[0041] It is worth mentioning that, as mentioned in the background technology, boron phenolic resin and ceramic particles are uniformly mixed to form a high-temperature resistant coating. For example, Chinese patent document No. CN 115473006 B discloses a polyimide composite diaphragm and its preparation method and sodium ion battery. However, the flammability of polyimide is relatively high, and it is impossible to quickly form a slow node disconnection mode with disconnection and disconnection at the positive and negative electrode puncture points. Therefore, in the present disclosure, since the fluorine-containing self-extinguishing polymer layer and the ceramic coating are respectively arranged on both sides of the base film, the fluorine-containing self-extinguishing polymer layer and the ceramic coating can better exert their respective characteristics separately, so as to quickly form a slow node disconnection mode with disconnection and disconnection at the positive and negative electrode puncture points, thereby effectively suppressing the problem that the traditional diaphragm cannot pass the puncture test due to large-area combustion caused by the high flammability of the diaphragm.
[0042] In this embodiment, the thermal shrinkage temperature of the slow node disconnect high temperature resistant composite diaphragm is as high as 250°C or more.
[0043] In one embodiment, the fluorine-containing self-extinguishing polymer layer includes at least one of PVDF polymers, polytetrafluoroethylene and polyperfluoroethylene propylene, so as to ensure that the formed fluorine-containing self-extinguishing polymer layer itself has good self-extinguishing properties and high-temperature heat shrinkage rate, thereby ensuring that a slow node disconnection mode with disconnection is formed more quickly at the positive and negative electrode puncture points.
[0044] In a preferred embodiment, the fluorine-containing self-extinguishing polymer layer is a PVDF polymer.
[0045] It is understandable that if the fluorine-containing self-extinguishing polymer layer has poor flexibility, then when it is punctured, the PVDF polymer cannot effectively disperse and absorb the stress generated by the puncture, and it is easy to rupture, causing direct contact between the positive and negative electrodes and causing internal short circuit problems; and if the fluorine-containing self-extinguishing polymer layer has insufficient flexibility, the material near the puncture site cannot effectively rebound or close, resulting in the expansion of the puncture hole diameter to increase the risk of direct contact between the positive and negative electrodes. Therefore, in the present disclosure, since PVDF polymers are high-performance thermoplastic fluoropolymers, in order to ensure that the PVDF polymers have high flexibility, it is also ensured that the fluorine-containing self-extinguishing polymer layer has good self-extinguishing properties and high-temperature thermal shrinkage rate, so as to ensure that the fluorine-containing self-extinguishing polymer layer can automatically and quickly extinguish the short-circuit heating that blocks the puncture point, thereby forming a slow node disconnection mode with disconnection at the positive and negative electrode puncture points, thereby effectively suppressing the traditional problem of large-scale combustion caused by the high flammability of the diaphragm and failing the puncture test; it is also ensured that the added PVDF polymer will not affect the overall electrical properties of the silicon-based ternary lithium battery, mainly because PVDF is also an adhesive used for silicon-based negative or positive electrodes.
[0046] It can also be understood that in actual applications, when the laminated silicon-based ternary lithium battery is fully charged, due to the embedding of lithium ions, the volume of the silicon-based negative electrode expands and becomes larger, resulting in a strong stress difference between the two sides of the silicon-based negative electrode, which causes the negative electrode active material of the silicon-based negative electrode to peel off the negative electrode current collector. Therefore, in the present disclosure, by controlling the formation temperature of the PVDF polymer to 80°C to 90°C, the surface energy of the PVDF polymer can be softened when the temperature of 80°C to 90°C is fully charged, so as to well suppress the problem of expansion and peeling of the silicon-carbon material.
[0047] In one of the embodiments, the molecular weight of PVDF is 400,000 Da to 500,000 Da, so as to ensure that the fluorine-containing self-extinguishing polymer layer has high flexibility, good self-extinguishing property and high-temperature heat shrinkage rate, thereby ensuring that a slow node disconnection mode with disconnection is quickly formed at the positive and negative electrode puncture points; at the same time, it also ensures that the PVDF polymer is well softened at 80°C to 90°C.
[0048] In one embodiment, the ceramic coating includes at least one of LATP (Lithiμm Alμminμm Titaniμm Phosphate) and LLZO (Lithiμm Lanthanμm Zirconiμm Oxide) to ensure that the ceramic coating has high temperature stability and the characteristics of delaying heat increase, which can significantly delay the rapid increase of heat during the puncture process and avoid the phenomenon of burning at the puncture site in a short time, thereby better solving the problem that the stacked silicon-based ternary lithium battery cannot pass the puncture test in practical applications.
[0049] It can also be understood that since LATP and LLZO have high ionic conductivity, they help to improve the capacity retention rate of stacked silicon-based ternary lithium batteries and reduce interface impedance, thereby ensuring the preparation of high-performance and high-rate stacked silicon-based ternary lithium batteries.
[0050] In one embodiment, the thickness of the fluorine-containing self-extinguishing polymer layer is 2 μm to 3 μm, so as to ensure that the fluorine-containing self-extinguishing polymer layer has high flexibility, good self-extinguishing property and good high-temperature heat shrinkage rate.
[0051] In one embodiment, the fluorine-containing self-extinguishing polymer layer is a high temperature resistant porous fluorine-containing self-extinguishing polymer layer, which is conducive to the fluorine-containing self-extinguishing polymer layer forming a slow node disconnection mode with disconnection at the positive and negative electrode puncture positions. Specifically, the high temperature resistant porous fluorine-containing self-extinguishing polymer layer has tiny pores, and the porosity of the high temperature resistant porous fluorine-containing self-extinguishing polymer layer is 38% to 42%.
[0052] In one embodiment, the base film is one of a PE base film and a PP base film. Since the PE base film and the PP base film are both prepared by a dry method, the prepared PE base film and the PP base film are ensured to have the characteristics of high temperature resistance, high mechanical strength and good chemical stability, thereby ensuring that the slow node disconnection high temperature resistant composite diaphragm has a higher heat shrinkage temperature.
[0053] In one embodiment, the PP base film is a uniaxially stretched PP base film. It can be understood that, compared with the biaxially stretched PP base film, the uniaxially stretched PP base film has a low transverse tensile strength, which is conducive to better breaking during acupuncture, so as to form a slow node disconnection mode with disconnection and disconnection at the positive and negative electrode puncture positions. In addition, since the uniaxially stretched PP base film has good hard elastic properties, it can ensure that the slow node disconnection and high temperature resistant composite diaphragm after being punctured still maintains good rigidity, thereby ensuring that the mechanical properties of the slow node disconnection and high temperature resistant composite diaphragm do not change significantly during the deformation process, that is, the slow node disconnection and high temperature resistant composite diaphragm outside the puncture position will not undergo obvious deformation, effectively avoiding the rapid diffusion of heat from the puncture position to the surroundings, so as to quickly form a slow node disconnection mode with disconnection and disconnection at the positive and negative electrode puncture positions.
[0054] The present disclosure also provides a method for preparing a slow-node-breaking high-temperature-resistant composite diaphragm, comprising the following steps: obtaining a base film; performing a corona operation on the base film to obtain a corona base film; preparing a first electrospinning solution containing a fluorine-containing self-extinguishing polymer; using the first electrospinning solution to perform a first electrospinning operation on the first surface of the corona base film to form a fluorine-containing self-extinguishing polymer layer on the first surface of the corona base film; preparing a second electrospinning solution containing ceramics; using the second electrospinning solution to perform a second electrospinning operation on the second surface of the corona base film to form a ceramic coating on the second surface of the corona base film to obtain the slow-node-breaking high-temperature-resistant composite diaphragm described in any of the above embodiments.
[0055] The preparation method of the slow node breaking high temperature resistant composite diaphragm is to perform the first corona operation and the second corona operation on the two sides of the uniaxially stretched PP base film respectively, so as to form a loose and irregular first porous structure on the first side of the uniaxially stretched PP base film, and form a dense and uniform second porous structure on the second side of the uniaxially stretched PP base film, especially in conjunction with the first electrostatic spinning operation, so as to form a high temperature resistant porous fluorine-containing self-extinguishing polymer layer; at the same time, in conjunction with the second electrostatic spinning operation, it is helpful to form a dense and uniform ceramic coating, so that the steel needle can penetrate The positive and negative electrodes short-circuit and generate heat at the moment of puncture, and the fluorine-containing self-extinguishing polymer layer at the puncture site shrinks and melts rapidly under high temperature conditions to form a break point, and the fluorine-containing self-extinguishing polymer layer can cover the inner wall of the puncture site after shrinking and melting at high temperature, which not only quickly forms a break at the periphery of the puncture site, but also improves the close bonding with the ceramic coating at the puncture site, so as to ensure that the ceramic coating at the puncture site can significantly delay the rapid increase of heat during the puncture process, and avoid the phenomenon of burning at the puncture site in a short time, which better solves the problem that the laminated silicon-based ternary lithium battery cannot pass the puncture test in practical applications.
[0056] like Figure 1 As shown, the slow node disconnection high temperature resistant composite diaphragm of one embodiment includes some or all of the following steps:
[0057] S101, obtaining a basement membrane.
[0058] It can be understood that the base film can provide better support for the fluorine-containing self-extinguishing polymer layer and the ceramic coating. Specifically, the base film is a uniaxially stretched PP base film. Compared with the biaxially stretched PP base film, the uniaxially stretched PP base film has a low transverse tensile strength, which is conducive to better breaking during acupuncture, so as to form a slow node disconnection mode with disconnection at the positive and negative electrode puncture positions. In addition, since the uniaxially stretched PP base film has good hard elastic properties, it can ensure that the slow node disconnection high temperature resistant composite diaphragm after being punctured still maintains good rigidity, thereby ensuring that the mechanical properties of the slow node disconnection high temperature resistant composite diaphragm do not change significantly during the deformation process, that is, the slow node disconnection high temperature resistant composite diaphragm outside the puncture position will not undergo obvious deformation, so as to better ensure that a slow node disconnection mode with disconnection is formed at the positive and negative electrode puncture positions.
[0059] In one embodiment, the thickness of the uniaxially stretched PP base film is 16 μm to 20 μm, and the porosity is 35% to 40%. 。
[0060] It can be understood that if the thickness of the uniaxially stretched PP base film is less than 16μm, the uniaxially stretched PP base film is prone to rupture during the subsequent corona operation; if the thickness of the uniaxially stretched PP base film is greater than 20μm, it cannot ensure that the positive and negative electrode puncture positions can quickly form a slow node disconnection mode with disconnection and disconnection, and the overall thickness of the uniaxially stretched PP base film is relatively thick, which affects the preparation of light, thin, high-performance, and high-rate laminated silicon-based ternary lithium batteries; if the porosity of the uniaxially stretched PP base film is greater than 40%, then High porosity will reduce the mechanical strength of the slow node disconnection high temperature resistant composite diaphragm, and increase the risk of internal short circuit in the laminated silicon-based ternary lithium battery; if the porosity of the uniaxially stretched PP base membrane is less than 35%, it cannot ensure that the steel needle of the puncture test can penetrate the uniaxially stretched PP base membrane well, and cannot quickly form a slow node disconnection mode with disconnection at the positive and negative electrode puncture positions, and the low porosity will also reduce the liquid absorption performance of the slow node disconnection high temperature resistant composite diaphragm, which is not conducive to improving the cycle performance of the silicon-based ternary lithium battery.
[0061] Therefore, in the present disclosure, by controlling the thickness of the uniaxially stretched PP base film to 16μm~20μm and the porosity to 35%~40%, the thickness and porosity of the uniaxially stretched PP base film are ensured to be more appropriate, so as to ensure that the steel needle of the puncture test can quickly penetrate the uniaxially stretched PP base film and quickly form a slow node disconnection mode with disconnection at the positive and negative electrode puncture positions; it also ensures that the slow node disconnection high temperature resistant composite diaphragm has good mechanical strength and is not prone to rupture during subsequent corona operations; it is also beneficial to improve the liquid absorption performance of the slow node disconnection high temperature resistant composite diaphragm, thereby facilitating the preparation of light and thin, high-performance, high-rate laminated silicon-based ternary lithium batteries.
[0062] S102, performing a corona treatment on the base film to obtain a corona base film.
[0063] It can be understood that since the surface energy of the base film, the fluorine-containing self-extinguishing polymer layer and the ceramic coating is relatively low, the base film needs to be corona treated to increase the contact area between the base film and the fluorine-containing self-extinguishing polymer layer and the ceramic coating, thereby improving the connection strength between the base film and the fluorine-containing self-extinguishing polymer layer and the ceramic coating.
[0064] It can also be understood that the presence of fluorine in the fluorine-containing self-extinguishing polymer layer will further reduce the surface energy of the fluorine-containing self-extinguishing polymer layer, resulting in the problem that the fluorine-containing self-extinguishing polymer layer is easy to fall off when using ordinary coating methods. Therefore, in one embodiment, the first surface of the uniaxially stretched PP base film is subjected to a first corona treatment operation to increase the roughness and surface area of the first surface of the uniaxially stretched PP base film, so that the surface of the first surface of the uniaxially stretched PP base film has higher adhesion, thereby improving the firmness of the connection between the first surface of the uniaxially stretched PP base film and the fluorine-containing self-extinguishing polymer layer.
[0065] In one of the embodiments, a second corona treatment is performed on the second side of the uniaxially stretched PP base film to increase the roughness and surface area of the second side of the uniaxially stretched PP base film, thereby making the surface of the second side of the uniaxially stretched PP base film have higher adhesion, thereby improving the firmness of the connection between the second side of the uniaxially stretched PP base film and the ceramic coating.
[0066] It should be noted that, since the fluorine-containing self-extinguishing polymer layer is usually an organic material, and the ceramic coating is an inorganic material, the fluorine-containing self-extinguishing polymer layer has a higher bonding property to the uniaxially stretched PP base film than the ceramic coating, and the ceramic coating is usually granular, resulting in the bonding force between the ceramic coating and the uniaxially stretched PP base film being worse than that between the fluorine-containing self-extinguishing polymer layer and the uniaxially stretched PP base film. Therefore, in the present disclosure, the conditions for the first corona operation are set as follows: point electrodes, an electrode gap of 2 mm to 3 mm, a voltage of 5000 to 10000 V / m 2 , using point electrodes to form a relatively loose and irregular first porous structure on the first surface of the uniaxially stretched PP base film, thereby facilitating the formation of a high-temperature resistant porous fluorine-containing self-extinguishing polymer layer on the first porous structure; in particular, the conditions for the second corona operation are: flat electrodes, an electrode gap of 1mm to 2mm, a voltage of 10000 to 15000V / m 2, so that the flat electrode can evenly cover the entire second side of the uniaxially stretched PP base film during the discharge process, so as to form a dense and uniform second porous structure on the second side of the uniaxially stretched PP base film, so that the granular ceramic coating can be well adhered to the second porous structure, which is helpful to form a dense and uniform ceramic coating; in this way, while satisfying the condition that the uniaxially stretched PP base film has good mechanical strength after the corona operation, it also ensures that the ceramic coating, the fluorine-containing self-extinguishing polymer layer and the uniaxially stretched PP base film have good connection strength, effectively avoiding the problem of easy falling off of the ceramic coating and the fluorine-containing self-extinguishing polymer layer.
[0067] It should also be noted that since the first side of the uniaxially stretched PP base film is a relatively loose and irregular first porous structure, on the one hand, it is beneficial to improve the connection strength between the fluorine-containing self-extinguishing polymer layer and the uniaxially stretched PP base film, and on the other hand, it is also beneficial to form a high-temperature resistant porous fluorine-containing self-extinguishing polymer layer on the first side of the uniaxially stretched PP base film, and a dense and uniform ceramic coating is formed on the second side of the uniaxially stretched PP base film, so that the dense and uniform ceramic coating can provide better mechanical support for the fluorine-containing self-extinguishing polymer layer and the uniaxially stretched PP base film. In this way, when performing a needle puncture test, the steel needle can penetrate the fluorine-containing self-extinguishing polymer layer, the uniaxially stretched PP base film and the ceramic coating, while ensuring that the high-temperature resistant porous fluorine-containing self-extinguishing polymer layer can shrink and melt to form a circuit break; it also effectively avoids the problem that the steel needle is difficult to penetrate the slow node circuit break high-temperature resistant composite diaphragm and affect the needle puncture test.
[0068] In one of the embodiments, before the step of performing corona operation on the base film, the method for preparing the slow node breaking high temperature resistant composite diaphragm also includes the following steps: performing surface treatment operation on the base film to effectively remove dust or stains on the base film, which is beneficial to improve the connection strength between the fluorine-containing self-extinguishing polymer layer, the ceramic coating and the uniaxially stretched PP base film.
[0069] In one of the embodiments, after the step of performing the surface treatment operation on the base film and before the step of the corona operation, the base film is preheated so that the heated base film will expand. On the one hand, it is convenient to perform the first corona operation and the second corona operation on both sides of the base film more comprehensively, thereby greatly improving the roughness area on both sides of the base film; on the other hand, it increases the flexibility of the base film, effectively avoiding the problem of the base film breaking during the first corona operation and the second corona operation.
[0070] Specifically, the base film is preheated at a temperature of 50° C. to 70° C. for a time of 10 min to 30 min.
[0071] S103, preparing a first electrospinning solution containing a fluorine-containing self-extinguishing polymer.
[0072] It can be understood that the fluorine-containing self-extinguishing polymer is mixed with an organic solvent to obtain the first electrospinning solution. Specifically, PVDF and dimethylformamide are mixed at a mass ratio of 1:10 to obtain the first electrospinning solution.
[0073] S104, performing a first electrospinning operation on the first surface of the corona base film using the first electrospinning liquid to form a fluorine-containing self-extinguishing polymer layer on the first surface of the corona base film.
[0074] It can be understood that by controlling the conditions of the first electrospinning operation: the first voltage is 10kV~25kV, the first spinning distance is 20cm~25cm, and the first extrusion speed is 0.02mL / min~0.2mL / min, it is ensured that a high temperature resistant and porous fluorine-containing self-extinguishing polymer layer is formed on the first surface of the corona base film.
[0075] S105, preparing a second electrospinning solution containing ceramics.
[0076] It can be understood that the ceramic particles are mixed with the organic solvent to obtain the second electrospinning solution. Specifically, lithium aluminum titanium phosphate particles or lithium lanthanum zirconium oxide are mixed with ethanol at a mass ratio of 1: (5-10) to obtain the second electrospinning solution.
[0077] In one embodiment, the particle size of lithium aluminum titanium phosphate particles is 100nm to 600nm. Specifically, in a preferred embodiment, the particle size of lithium aluminum titanium phosphate particles is 300nm to 600nm to ensure a dense and uniform ceramic coating so that the steel needle can form a slow node disconnection mode at the positive and negative electrode puncture positions.
[0078] In one embodiment, the particle size of lithium lanthanum zirconium oxide particles is 20 μm to 80 μm to ensure the formation of a relatively dense and uniform ceramic coating, so that the steel needle can form a slow node disconnection mode at the positive and negative electrode puncture points to break the circuit.
[0079] It should be noted that if only lithium aluminum titanium phosphate particles with smaller particle size are used, a denser ceramic coating will be formed on the second side of the base film, resulting in a stronger rigidity of the ceramic coating and more serious damage to the steel needle; if only lithium lanthanum zirconium oxide particles with larger particle size are used, the ceramic coating will be more loose and unable to provide the base film with better high temperature resistance, thereby failing to ensure that the slow node disconnection high temperature resistant composite diaphragm can form a slow node disconnection mode of disconnection and disconnection when punctured; and when a ceramic coating of lithium lanthanum zirconium oxide with larger particle size is used, the large particles of lithium lanthanum zirconium oxide at the edge of the puncture site are easily punctured by the steel needle when the steel needle is punctured, causing the ceramic coating at the puncture site to easily crack and affect the reduction of the shrinkage fullness of the puncture site, and failing to effectively delay the heat around the puncture site, resulting in a sharp increase in heat, resulting in a relatively large shrinkage of the base film and an increased probability of short circuit between the positive and negative electrodes. Therefore, in a preferred embodiment, the ceramic particles are a mixture of lithium aluminum titanium phosphate particles and lithium lanthanum zirconium oxide particles, so that the lithium aluminum titanium phosphate particles with smaller particle size and the lithium lanthanum zirconium oxide particles with larger particle size can form a ceramic coating with suitable density and rigidity, thereby reducing damage to the steel needle and ensuring that the ceramic coating at the puncture site is not prone to cracking, so as to ensure that the ceramic coating at the puncture site can effectively block the heat from the puncture from being quickly transferred to the surroundings, thereby delaying the rapid increase in heat during the puncture process, and effectively avoiding the problem of large shrinkage of the base film and increased probability of short circuit between the positive and negative electrodes.
[0080] In a more preferred embodiment, the mass ratio of lithium aluminum titanium phosphate particles to lithium lanthanum zirconium oxide particles is 2:1 to ensure the formation of a ceramic coating with suitable density and rigidity. It is worth mentioning that suitable density refers to a certain degree of bulkiness, thereby avoiding the high rigidity of the ceramic coating, so that the steel needle can quickly pass through the positive and negative electrode puncture sites, especially with the use of high-temperature resistant porous fluorine-containing self-extinguishing polymer layers, to ensure that the steel needle can quickly pass through the positive and negative electrode puncture sites, and at the same time ensure that the ceramic coating at the puncture site is not easy to crack, to ensure that the ceramic coating at the puncture site can effectively block the heat from the puncture to the surrounding area, thereby delaying the rapid increase in heat during the puncture process, effectively avoiding the problem of large shrinkage of the base film and increasing the probability of short circuit of the positive and negative electrodes, and better solving the problem that the laminated silicon-based ternary lithium battery cannot pass the puncture test in practical applications.
[0081] S106. Perform a second electrospinning operation on the second surface of the corona base film using the second electrospinning liquid to form a ceramic coating on the second surface of the corona base film to obtain the slow node breaking high temperature resistant composite diaphragm described in any of the above embodiments.
[0082] In one embodiment, the conditions of the second electrospinning operation are: the second voltage is 15kV to 30kV, the second spinning distance is 15cm to 20cm, and the second extrusion speed is 0.05mL / min to 0.3mL / min, so as to ensure that a ceramic coating with suitable density and rigidity is formed on the second side of the uniaxially stretched PP base film.
[0083] The preparation method of the slow node breaking high temperature resistant composite diaphragm is to perform the first corona operation and the second corona operation on the two sides of the uniaxially stretched PP base film respectively, so as to form a loose and irregular first porous structure on the first side of the uniaxially stretched PP base film, and form a dense and uniform second porous structure on the second side of the uniaxially stretched PP base film, especially in conjunction with the first electrostatic spinning operation, so as to form a high temperature resistant porous fluorine-containing self-extinguishing polymer layer; at the same time, in conjunction with the second electrostatic spinning operation, it is helpful to form a dense and uniform ceramic coating, so that the steel needle can penetrate The positive and negative electrodes short-circuit and generate heat at the moment of puncture, and the fluorine-containing self-extinguishing polymer layer at the puncture site shrinks and melts rapidly under high temperature conditions to form a break point, and the fluorine-containing self-extinguishing polymer layer can cover the inner wall of the puncture site after shrinking and melting at high temperature, which not only quickly forms a break at the periphery of the puncture site, but also improves the close bonding with the ceramic coating at the puncture site, so as to ensure that the ceramic coating at the puncture site can significantly delay the rapid increase of heat during the puncture process, and avoid the phenomenon of burning at the puncture site in a short time, which better solves the problem that the laminated silicon-based ternary lithium battery cannot pass the puncture test in practical applications.
[0084] The present disclosure also provides a laminated silicon-based ternary lithium battery, comprising a positive electrode sheet, a silicon-based negative electrode sheet and a diaphragm stacked in sequence, wherein the diaphragm is prepared using the slow node disconnection high temperature resistant composite diaphragm described in any of the above embodiments.
[0085] It can be understood that the slow node breaking high temperature resistant composite diaphragm disclosed in the present invention is applied to the laminated silicon-based ternary lithium battery, so that the puncture point of the slow node breaking high temperature resistant composite diaphragm shrinks and melts at the moment the steel needle passes through, so that the positive and negative electrode puncture points form a circuit break and are not connected, thereby further suppressing the short-circuit heating of the laminated silicon-based ternary lithium battery during puncture and causing thermal runaway.
[0086] In one of the embodiments, the capacity ratio of the negative electrode capacity N to the positive electrode capacity P of the laminated silicon-based ternary lithium battery is 1.2 to 1.3, which effectively reduces the activity of the silicon-based negative electrode, making the intensity of the active reaction of the silicon-based negative electrode during short circuit lower than that of the normally designed silicon-based negative electrode, thereby ensuring that the laminated silicon-based ternary lithium battery can pass the puncture test more safely.
[0087] Compared with the prior art, the present invention has at least the following advantages:
[0088] 1) Compared with the traditional boron phenolic resin, the fluorine-containing self-extinguishing polymer layer contains fluorine atoms, which have high electronegativity and low polarizability, so that the interaction between the molecular chains of the fluorine-containing self-extinguishing polymer layer is strong and not easy to burn. In addition, the presence of fluorine atoms also improves the chemical resistance and thermal stability of the fluorine-containing self-extinguishing polymer layer, and because the fluorine-containing self-extinguishing polymer layer itself has self-extinguishing properties, when the laminated silicon-based ternary lithium battery is punctured, the fluorine-containing self-extinguishing polymer layer at the puncture site shrinks and melts under high temperature conditions and forms a short circuit, that is, the positive and negative puncture sites form a slow node disconnection mode with a short circuit, thereby effectively suppressing the problem that the traditional diaphragm cannot pass the puncture test due to large-scale combustion caused by high flammability.
[0089] 2) Since the fluorine-containing self-extinguishing polymer layer usually has high flexibility and relatively low mechanical strength, when passing the puncture test, if the diaphragm of the simple fluorine-containing self-extinguishing polymer layer is easily deformed or broken, there is still the problem of short circuit at the puncture site, that is, it cannot pass the puncture test. Therefore, the ceramic coating added in the present disclosure has the characteristics of high temperature stability and delayed heat increase, so that the fluorine-containing self-extinguishing polymer layer at the puncture site undergoes rapid high-temperature shrinkage and melting under high temperature conditions to form a break point, and after high-temperature shrinkage and melting, the fluorine-containing self-extinguishing polymer layer can cover the inner peripheral wall of the puncture site, not only quickly forming a break at the periphery of the puncture site, but also improving the close combination with the ceramic coating at the puncture site, so as to ensure that the ceramic coating at the puncture site can significantly delay the rapid increase of heat during the puncture process, avoid the phenomenon of burning at the puncture site in a short time, and better solve the problem that the laminated silicon-based ternary lithium battery cannot pass the puncture test in practical applications.
[0090] 3) In addition, the added fluorine-containing self-extinguishing polymer layer is also beneficial during the formation stage. As the formation temperature increases, the surface softening can occur, so that the fluorine-containing self-extinguishing polymer layer can effectively inhibit the expansion and peeling of the silicon-carbon material, and as the formation temperature decreases, it becomes hard and is beneficial to the shrinkage of the silicon-carbon material after lithium removal, so as to facilitate the preparation of high-performance and high-rate laminated silicon-based ternary lithium batteries.
[0091] Compared with the prior art, the present invention has at least the following advantages:
[0092] Some specific examples are given below, and if % is mentioned, it means percentage by weight. It should be noted that the following examples do not exhaust all possible situations, and the materials used in the following examples can be obtained from commercial sources unless otherwise specified.
[0093] Example 1
[0094] S1, obtaining a uniaxially stretched PP base film with a thickness of 16 μm and a porosity of 40%;
[0095] S2. Surface treatment of the uniaxially stretched PP base film to remove dust or stains;
[0096] S3, preheating the uniaxially stretched PP base film at a temperature of 50° C. for 10 min;
[0097] S4, use point electrodes to perform the first corona operation on the first side of the uniaxially stretched PP base film, and control the gap of the point electrodes to be 3mm and the voltage to be 8000V / m 2 , so as to form a relatively loose and irregular first porous structure on the first surface of the uniaxially stretched PP base film;
[0098] S5. Use a flat electrode to perform a second corona operation on the second side of the uniaxially stretched PP base film, and control the gap between the flat electrodes to 2mm and the voltage to 12000V / m 2 , so as to form a dense and uniform second porous structure on the second surface of the uniaxially stretched PP base film;
[0099] S6, preparing a first electrospinning solution of a fluorine-containing self-extinguishing polymer: mixing PVDF (molecular weight 400,000 Da) and dimethylformamide at a mass ratio of 1:10 to obtain a first electrospinning solution;
[0100] S7, performing a first electrospinning operation on the first side of the uniaxially stretched PP base film using a first electrospinning solution to form a fluorine-containing self-extinguishing polymer layer (with a thickness of 2 μm) on the first side of the uniaxially stretched PP base film, and controlling the conditions of the first electrospinning operation: the first voltage is 10 kV, the first spinning distance is 20 cm, and the first extrusion speed is 0.1 mL / min;
[0101] S8, preparing a second electrospinning solution containing ceramics: mixing lithium aluminum titanium phosphate particles (manufacturer: Dongguan Hongkai Electronic Technology Co., Ltd.; particle size: 300 nm) and ethanol at a mass ratio of 1:6 to obtain a second electrospinning solution;
[0102] S9. Use a second electrospinning liquid to perform a second electrospinning operation on the first side of the uniaxially stretched PP base membrane, and control the conditions of the second electrospinning operation: the second voltage is 25 kV, the second spinning distance is 15 cm, and the second extrusion speed is 0.2 mL / min, so as to form a ceramic coating (with a thickness of 2 μm) on the second side of the uniaxially stretched PP base membrane to obtain a slow-node-breaking high-temperature resistant composite diaphragm.
[0103] Example 2
[0104] S1, obtaining a uniaxially stretched PP base film with a thickness of 20 μm and a porosity of 38%;
[0105] S2. Surface treatment of the uniaxially stretched PP base film to remove dust or stains;
[0106] S3, preheating the uniaxially stretched PP base film at 60°C for 30 minutes;
[0107] S4, use point electrodes to perform the first corona operation on the first side of the uniaxially stretched PP base film, and control the gap of the point electrodes to be 2mm and the voltage to be 10000V / m 2 , so as to form a relatively loose and irregular first porous structure on the first surface of the uniaxially stretched PP base film;
[0108] S5. Use a flat electrode to perform a second corona operation on the second side of the uniaxially stretched PP base film, and control the gap between the flat electrodes to 1mm and the voltage to 15000V / m 2 , so as to form a dense and uniform second porous structure on the second surface of the uniaxially stretched PP base film;
[0109] S6, preparing a first electrospinning solution of a fluorine-containing self-extinguishing polymer: mixing PVDF (molecular weight 450,000 Da) and dimethylformamide at a mass ratio of 1:10 to obtain a first electrospinning solution;
[0110] S7, using the first electrospinning solution to perform a first electrospinning operation on the first side of the uniaxially stretched PP base film to form a fluorine-containing self-extinguishing polymer layer (with a thickness of 3 μm) on the first side of the uniaxially stretched PP base film, and controlling the conditions of the first electrospinning operation: the first voltage is 25 kV, the first spinning distance is 25 cm, and the first extrusion speed is 0.2 mL / min;
[0111] S8, preparing a second electrospinning solution containing ceramics: mixing lithium lanthanum zirconium oxide particles (manufactured by Shanghai Jiader Chemical Technology Co., Ltd.; particle size 20 μm) and ethanol at a mass ratio of 1:8 to obtain a second electrospinning solution;
[0112] S9. Use a second electrospinning liquid to perform a second electrospinning operation on the first side of the uniaxially stretched PP base membrane, and control the conditions of the second electrospinning operation: the second voltage is 30 kV, the second spinning distance is 20 cm, and the second extrusion speed is 0.3 mL / min, so as to form a ceramic coating (with a thickness of 1 μm) on the second side of the uniaxially stretched PP base membrane to obtain a slow-node-breaking high-temperature resistant composite diaphragm.
[0113] Example 3
[0114] S1, obtaining a uniaxially stretched PP base film with a thickness of 18 μm and a porosity of 35%;
[0115] S2. Surface treatment of the uniaxially stretched PP base film to remove dust or stains;
[0116] S3, preheating the uniaxially stretched PP base film at a temperature of 55° C. for 20 minutes;
[0117] S4, use point electrodes to perform the first corona operation on the first side of the uniaxially stretched PP base film, and control the gap of the point electrodes to be 2.5mm and the voltage to be 5000V / m 2 , so as to form a relatively loose and irregular first porous structure on the first surface of the uniaxially stretched PP base film;
[0118] S5. Use a flat electrode to perform a second corona operation on the second side of the uniaxially stretched PP base film, and control the gap between the flat electrodes to 1.5 mm and the voltage to 10000 V / m. 2 , so as to form a dense and uniform second porous structure on the second surface of the uniaxially stretched PP base film;
[0119] S6, preparing a first electrospinning solution of a fluorine-containing self-extinguishing polymer: mixing PVDF (molecular weight 500,000 Da) and dimethylformamide at a mass ratio of 1:10 to obtain a first electrospinning solution;
[0120] S7, using the first electrospinning solution to perform a first electrospinning operation on the first side of the uniaxially stretched PP base film to form a fluorine-containing self-extinguishing polymer layer (with a thickness of 2.5 μm) on the first side of the uniaxially stretched PP base film, and controlling the conditions of the first electrospinning operation: the first voltage is 15 kV, the first spinning distance is 23 cm, and the first extrusion speed is 1.2 mL / min;
[0121] S8, preparing a second electrospinning solution containing ceramics: mixing lithium aluminum titanium phosphate particles (manufacturer: Dongguan Hongkai Electronic Technology Co., Ltd.; particle size: 600 nm) and ethanol at a mass ratio of 1:8 to obtain a second electrospinning solution;
[0122] S9. Use a second electrospinning liquid to perform a second electrospinning operation on the first side of the uniaxially stretched PP base membrane, and control the conditions of the second electrospinning operation: the second voltage is 18 kV, the second spinning distance is 18 cm, and the second extrusion speed is 0.18 mL / min, so as to form a ceramic coating (with a thickness of 4 μm) on the second side of the uniaxially stretched PP base membrane to obtain a slow-node-breaking high-temperature resistant composite diaphragm.
[0123] Comparative Example 1
[0124] The difference from Example 1 is that the steps S8 and S9 are omitted in Comparative Example 1, and the rest remain unchanged.
[0125] Comparative Example 2
[0126] The difference from Example 1 is that the steps S6 and S7 are omitted in Comparative Example 2, and the rest remain unchanged.
[0127] Comparative Example 3
[0128] The difference from Example 1 is that the S3 step is omitted in Comparative Example 3, and the rest remains unchanged.
[0129] Comparative Example 4
[0130] The difference from Example 1 is that the S4 step is omitted in Comparative Example 4, and the rest remains unchanged.
[0131] Comparative Example 5
[0132] The difference from Example 1 is that the step S5 is omitted in Comparative Example 5, and the rest remains unchanged.
[0133] Comparative Example 6
[0134] The difference from Example 1 is that the lithium aluminum titanium phosphate particles in Example 1 are replaced by a mixture of lithium aluminum titanium phosphate particles and lithium lanthanum zirconium oxide particles, and the mass ratio of the lithium aluminum titanium phosphate particles to the lithium lanthanum zirconium oxide particles is 2:1, and the rest remains unchanged.
[0135] The slow node disconnection high temperature resistant composite diaphragm, silicon-based negative electrode sheet and ternary positive electrode sheet prepared in the above-mentioned embodiments 1 to 3 and comparative examples 1 to 6 are prepared by an alternating positive and negative electrode sheet stacking process to obtain a laminated silicon-based ternary lithium battery, and the capacity ratio of the negative electrode capacity N to the positive electrode capacity P of the laminated silicon-based ternary lithium battery is controlled to be 1.2 to 1.3, and the laminated silicon-based ternary lithium battery is subjected to a needle puncture test to obtain the experimental data in Table 1.
[0136] Needle puncture test conditions: After the laminated silicon-based ternary lithium battery is fully charged, use a Φ4mm (modified to 5mm) high-temperature resistant steel needle (the cone angle of the needle tip is 45-60°, the needle surface is smooth, free of rust, oxide layer and oil), at a speed of (25±5)mm / s, to penetrate from a direction perpendicular to the laminated silicon-based ternary lithium battery. The penetration position is close to the geometric center of the punctured surface. The steel needle stays in the laminated silicon-based ternary lithium battery. The time the steel needle passes through is recorded, and observe whether there is fire or explosion within 1h.
[0137] Surface inspection of puncture sites: visual inspection after disassembling the stacked silicon-based ternary lithium battery.
[0138] The shrinkage rate of the slow node breaking high temperature resistant composite diaphragm after puncture: first measure the transverse and longitudinal dimensions of the slow node breaking high temperature resistant composite diaphragm before puncture. After the puncture test is completed, disassemble the stacked silicon-based ternary lithium battery, and measure the transverse and longitudinal dimensions of the slow node breaking high temperature resistant composite diaphragm respectively to calculate the transverse and longitudinal shrinkage rates of the slow node breaking high temperature resistant composite diaphragm at the puncture position.
[0139] Table 1
[0140]
[0141]
[0142] From the comparison of Examples 1 to 3 and Comparative Examples 1 to 5 in the above table, it can be seen that since Examples 1 to 3 use a uniaxially stretched PP base film as the base film, and the first corona operation, the second corona operation, the first electrospinning operation and the second electrospinning operation are respectively performed on both sides of the uniaxially stretched PP base film, so as to form a fluorine-containing self-extinguishing polymer layer and a ceramic coating on both sides of the base film, respectively, to ensure that the slow node disconnection high temperature resistant composite diaphragm can form a slow node disconnection mode of disconnection and disconnection around the puncture position when passing the needle puncture, which better solves the problem that the laminated silicon-based ternary lithium battery cannot pass the needle puncture test in practical applications. For details, please refer to Figure 2 Example 1 is a practical comparison diagram before and after acupuncture.
[0143] From the comparison of Example 1 and Comparative Example 6 in the above table, it can be seen that since the ceramic coating of Comparative Example 6 is a mixture of lithium titanium aluminum phosphate particles and lithium lanthanum zirconium oxide particles, it can reduce damage to the steel needles, while ensuring that the ceramic coating at the puncture site is not prone to cracking or blackening, so as to ensure that the ceramic coating at the puncture site can effectively block the heat from the puncture to be quickly transferred to the surroundings, and effectively delay the rapid increase in heat during the puncture process, thereby avoiding a large shrinkage rate of the slow-node-breaking high-temperature resistant composite diaphragm after puncture, so that the shrinkage rate of the slow-node-breaking high-temperature resistant composite diaphragm after puncture of Comparative Example 6 is better than that of Example 1.
[0144] The above-mentioned embodiments only express several implementation methods of the present disclosure, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the disclosed patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present disclosure, and these all belong to the protection scope of the present disclosure. Therefore, the protection scope of the disclosed patent shall be subject to the attached claims.
Claims
1. A slow node breaking high temperature resistant composite diaphragm, characterized in that: It includes a base film, a fluorine-containing self-extinguishing polymer layer and a ceramic coating. The fluorine-containing self-extinguishing polymer layer and the ceramic coating are respectively arranged on the two sides of the base film. The fluorine-containing self-extinguishing polymer layer is used to shrink and melt the slow-node disconnection high-temperature resistant composite diaphragm when it is punctured, and form a disconnection at the puncture position.
2. The slow node breaking high temperature resistant composite diaphragm according to claim 1 is characterized in that: The fluorine-containing self-extinguishing polymer layer includes at least one of PVDF polymer, polytetrafluoroethylene and polyperfluoroethylene-propylene.
3. The slow node breaking high temperature resistant composite diaphragm according to claim 2 is characterized in that: The molecular weight of the PVDF polymer is 400,000 Da to 500,000 Da.
4. The slow node breaking high temperature resistant composite diaphragm according to claim 1, characterized in that: The ceramic coating includes at least one of LATP and LLZO.
5. The slow node breaking high temperature resistant composite diaphragm according to claim 1 is characterized in that: The thickness of the fluorine-containing self-extinguishing polymer layer is 2 μm to 3 μm; and / or, The fluorine-containing self-extinguishing polymer layer is a high temperature resistant porous fluorine-containing self-extinguishing polymer layer.
6. The slow node breaking high temperature resistant composite diaphragm according to claim 1, characterized in that: The base film is a PE base film or a PP base film.
7. A method for preparing a slow node breaking high temperature resistant composite diaphragm, characterized in that: The steps include: Obtaining basement membrane; Performing a corona treatment on the base film to obtain a corona base film; preparing a first electrospinning solution containing a fluorine-containing self-extinguishing polymer; Performing a first electrospinning operation on the first surface of the corona base film using the first electrospinning solution to form a fluorine-containing self-extinguishing polymer layer on the first surface of the corona base film; preparing a second electrospinning solution containing ceramics; The second electrospinning liquid is used to perform a second electrospinning operation on the second surface of the corona base film to form a ceramic coating on the second surface of the corona base film, so as to obtain the slow node breaking high temperature resistant composite diaphragm according to any one of claims 1 to 7.
8. The method for preparing the slow node breaking high temperature resistant composite diaphragm according to claim 7, characterized in that: Before the step of performing corona treatment on the base film, the method for preparing the slow node disconnection high temperature resistant composite diaphragm further comprises the following step: performing surface treatment on the base film.
9. The method for preparing the slow node breaking high temperature resistant composite diaphragm according to claim 7, characterized in that: The conditions of the first electrospinning operation are: a first voltage of 10 kV to 25 kV, a first spinning distance of 15 cm to 20 cm, and a first extrusion speed of 0.02 mL / min to 0.3 mL / min; and / or, The conditions of the second electrospinning operation are as follows: the second voltage is 10 kV to 25 kV, the second spinning distance is 15 cm to 20 cm, and the second extrusion speed is 0.02 mL / min to 0.3 mL / min.
10. A laminated silicon-based ternary lithium battery, comprising a positive electrode sheet, a silicon-based negative electrode sheet and a diaphragm stacked in sequence, characterized in that: The diaphragm is prepared by using the slow node breaking high temperature resistant composite diaphragm described in any one of claims 7 to 9.
Citation Information
Patent Citations
A polyimide composite diaphragm and preparation method thereof and sodium ion battery
CN115473006B
Coated diaphragm with high temperature resistance and puncture resistance and preparation method thereof
CN116247371A